Flaxseed extract: A potential therapeutic intervention for type-2 diabetes mellitus and cardiovascular risk reduction in Wistar rats - Patonah Hasimun; Herni Kusriani; Yani Mulyani; Nurasyfa Syaumi (Journal of HerbMed Pharmacology)
Introduction: Type 2 diabetes mellitus (T2DM) affects millions of people worldwide, highlighting the importance of dietary interventions. Flaxseed (Linum usitatissimum L.) has shown promise in treating chronic metabolic diseases. This study investigates the therapeutic potential of flaxseed as an antidiabetic agent and its protective effect on cardiovascular diseases. Methods: Rats were randomly divided into five groups: normal fed with drug carrier group (N), diabetes with drug carrier group (D), diabetes with metformin (M) group (D+M), and diabetes with flaxseed extract doses of 100 and 200 mg/kg (D+F1 and D+F2) groups. The diabetic rat model was established by administration of drinking water containing 25% fructose and a single intraperitoneal injection of 100 mg/kg alloxan. After a six-week intervention, the rats were sacrificed to assess the antidiabetic and cardiovascular effects. Results: The doses of 100 and 200 mg/kg flaxseed extract significantly reduced body weight and fasting glucose levels and increased insulin sensitivity index (KITT) compared to the diabetes group (P<0.05). In addition, histological analysis showed a significant improvement and increase in pancreatic beta cells in the treatment group compared to the diabetes group (P<0.05). Flaxseed extract doses of 100 and 200 mg/kg significantly reduced weight gain and insulin resistance, contributing to decreased arterial stiffness and atherogenic index compared to the diabetic group (P<0.05). The hypoglycemic effect suggested a dose-dependent response. Conclusion: Flaxseed extract regulates blood glucose levels probably by enhancing insulin sensitivity and revitalizing damaged pancreatic beta cells. It mitigates cardiovascular risk, by reducing arterial stiffness and atherogenicity.